Determination of Factors Affecting Sustainable Development of the Insurance Market in Ukraine - Sholoiko, Antonina; Shevchenko, Liudmyla (<center>Conference Proceedings Determinants Of Regional Development</center>; No 2 (2021): Conference Proceedings - VIII International Scientific Conference Determinants of Regional DevelopmentDO - 10.14595/CP/02/004, 2021)
Determination of the most influential factors affecting sustainable development of the insurance market is quite important for providing sustainable economy. In this context, information plays a great role in the decision-making process of government authorities, providers and consumers of insurance services. So it is necessary to define what information may be useful. The goal of the research is to select complex factors affecting sustainable development of the insurance market using the case of the Ukrainian insurance market. It was done with the help of factor analysis (selection method: principal component analysis; rotation method: varimax) in SPSS using open data of Ukrainian government institutions (2001-2018 years). The research made it possible to determine among 10 factors (average salary of physical entities, inflation rate, number of insurers, level of insurance payments, number of insurance brokers, insurance reserves, assets of insurers, charter capital of insurers, insurance density, share of foreign reinsurance premiums in total insurance premiums) 2 significant complex factors: solvency of insurers and solvency of consumers of insurance services affecting sustainable development of the insurance market of Ukraine. These results mean that it is necessary to decrease influence of these complex factors under implementation of Directive 2009/138/EC Solvency II into institutional  environments of the Ukrainian insurance market under conditions of implementation of European integration vector by financial and other authorities of Ukraine. For sustainable development of the insurance market of Ukraine, it is essential to create and implement national and regional programs of sustainable development of the insurance market of Ukraine. The structure of such programs is suggested.